Direct photon production at low transverse momentum in proton-proton collisions at √s=2.76 and 8 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Physical review, 2019)
Measurements of inclusive and direct photon production at midrapidity in pp collisions at √s=2.76 and 8 TeV are presented by the ALICE experiment at the LHC. The results are reported in transverse momentum ranges of 0.4<pT<10 GeV/c and 0.3<pT<16 GeV/c, respectively. Photons are detected with the electromagnetic calorimeter (EMCal) and via reconstruction of e+e− pairs from conversions in the ALICE detector material using the central tracking system. For the final measurement of the inclusive photon spectra the results are combined in the overlapping pT interval of both methods. Direct photon spectra, or their upper limits at 90% C.L. are extracted using the direct photon excess ratio Rγ, which quantifies the ratio of inclusive photons over decay photons generated with a decay-photon simulation. An additional hybrid method, combining photons reconstructed from conversions with those identified in the EMCal, is used for the combination of the direct photon excess ratio Rγ, as well as the extraction of direct photon spectra or their upper limits. While no significant signal of direct photons is seen over the full pT range, Rγ for pT>7 GeV/c is at least one σ above unity and consistent with expectations from next-to-leading order pQCD calculations.
Gesehen am 24.04.2019
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und 985 weitere]
ganzer Ausdruck "s=2.76" steht unter dem Wurzelzeichen